2021
DOI: 10.2196/20330
|View full text |Cite
|
Sign up to set email alerts
|

mHealth Interventions for Treatment Adherence and Outcomes of Care for Cardiometabolic Disease Among Adults Living With HIV: Systematic Review

Abstract: Background The success of antiretroviral therapy has led to an increase in life expectancy and an associated rise in the risk of cardiometabolic diseases (CMDs) among people living with HIV. Objective Our aim was to conduct a systematic review to synthesize the existing literature on the patterns of use and effects of mobile health (mHealth) interventions for improving treatment adherence and outcomes of care for CMD among people living with HIV. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Throughout Africa, many pilot mHealth interventions have been launched to manage Ebola ( Tom-Aba et al, 2018 ), maternal health ( Ag Ahmed et al, 2017 ; Mildon and Sellen, 2019 ; Onukwugha et al, 2022 ), and various childhood ailments ( Mahmood et al, 2020 ). To date, the majority of mHealth interventions that have been implemented in Africa have focused on using SMS/texting to improve treatment adherence and patient retention ( Kruse et al, 2019 ; Manby et al, 2022 ; Odukoya et al, 2021 ); notably, such interventions only require access to BPs. Studies of these interventions have shown that weekly text messaging to HIV patients that are literate (and voice-enabled systems for illiterate patients) have substantially improved adherence to medication and increased retention in care.…”
Section: Discussionmentioning
confidence: 99%
“…Throughout Africa, many pilot mHealth interventions have been launched to manage Ebola ( Tom-Aba et al, 2018 ), maternal health ( Ag Ahmed et al, 2017 ; Mildon and Sellen, 2019 ; Onukwugha et al, 2022 ), and various childhood ailments ( Mahmood et al, 2020 ). To date, the majority of mHealth interventions that have been implemented in Africa have focused on using SMS/texting to improve treatment adherence and patient retention ( Kruse et al, 2019 ; Manby et al, 2022 ; Odukoya et al, 2021 ); notably, such interventions only require access to BPs. Studies of these interventions have shown that weekly text messaging to HIV patients that are literate (and voice-enabled systems for illiterate patients) have substantially improved adherence to medication and increased retention in care.…”
Section: Discussionmentioning
confidence: 99%
“…This could be viewed as a potential pitfall unless further innovation is made in this field, as patients are more likely to respond positively to a readily available app on their smartphone [ 74 ]. Most research in other medical fields has concluded that telephone or videoconferencing calls are the most popular intervention, further emphasizing the need for more development [ 75 , 76 ]. It is important that development continues, as reports suggest that patients feel there is a lack of currently available, relevant high-quality mHealth apps providing adequate support [ 77 ].…”
Section: Discussionmentioning
confidence: 99%